Sinonasal adenocarcinoma - hospital de braga ent department expertise - Breda, Miguel (2017)
Introduction: The nasal adenocarcinoma (AD) represents about 20% of cases of sinonasal malignancy. Endoscopic surgery (FESS) has gained preponderance for its treatment. In advanced stages, the craniofacial resection remain as an option, however the combined approach can be considered.Objective and Methods: Retrospective analysis, between 2002 and 2014, of 14 AD cases diagnosed and treated in our department.Results: The series consists of 14 patients with mean age of 60 years, and 11 with advanced stage at diagnosis. It was adopted, in 5 cases, an external surgical approach, in 6 FESS, and in 1 a combined approach. 5-years-overall- survival rate was 40%.Conclusion: 2 and 5-years-survival rate is similar to other series already published.